Lithium secondary battery

CN121100432BActive Publication Date: 2026-10-09LG ENERGY SOLUTION LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202480032132.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2024-11-19
Filing Date
2024-11-20
Publication Date
2026-10-09
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

[0010]然而,由于高负载电极不仅活性材料涂布的程度高,而且还被设计为提高电极密度,因此电极压缩的程度非常大,因此存在由于电极中的多孔结构不足而导致电解质浸渍性降低的缺点

Benefits of technology

[0037] Because the electrolyte used in the lithium secondary battery of the present invention includes an organic solvent containing a cyclic lactone compound as the main solvent and lithium nitrate (LiNO3) as an additive in an amount controlled according to the loading of the positive electrode, the electrolyte impregnation of the high-load positive electrode can be improved, and a film with low resistance can be formed on the surface of the high-load positive electrode, thereby improving the charge mobility on the surface of the high-load positive electrode. Therefore, the cycle characteristics and high-temperature storage characteristics of the lithium secondary battery of the present invention can be improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121100432B_ABST
    Figure CN121100432B_ABST
Patent Text Reader

Abstract

This invention relates to a lithium secondary battery with improved high-temperature cycling characteristics. Specifically, it relates to a lithium secondary battery comprising a positive electrode, a negative electrode, a separator, and an electrolyte. The positive electrode comprises lithium iron phosphate as the positive electrode active material, and the electrolyte comprises a lithium salt, a first organic solvent, a second organic solvent, and an additive. The first organic solvent is a cyclic lactone compound, the second organic solvent is a carbonate organic solvent, and the additive is lithium nitrate (LiNO3), satisfying the following relationship 1: [Relationship 1] In Relationship 1, A is the total amount of electrolyte injected into the lithium secondary battery (g), B is the amount (wt%) of lithium nitrate (LiNO3) contained in the injected electrolyte, and C is the positive electrode loading (g / cm³). 2 ), and D is the total surface area of ​​the positive electrode current collector (cm²). 2 ).
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Cross-references to related applications

[0002] This application claims priority to Korean Patent Application No. 10-2023-0189753, filed on December 22, 2023, and Korean Patent Application No. 10-2024-0165719, filed on November 19, 2024, the disclosures of which are incorporated herein by reference. Technical Field

[0003] This invention relates to a lithium secondary battery, and to a lithium secondary battery having improved high-temperature cycling characteristics. Background Technology

[0004] Recently, as the application of lithium secondary batteries has rapidly expanded not only to the power, electronics, communications, and electronic devices such as computers, but also to the power storage supply of automobiles or large-area devices (such as power storage devices), the demand for secondary batteries with high stability, high capacity, and high output is increasing.

[0005] In particular, in order to use lithium secondary batteries as a power source for electric vehicles, lithium secondary batteries must be able to stably generate high output at high temperatures and high voltages. For this purpose, the use of negative electrode active materials such as lithium metal, carbon compounds and silicon compounds, as well as high-nickel positive electrode active materials with high energy density, is being considered.

[0006] However, high-nickel cathode active materials suffer from a significant limitation in their usable SOC range due to a sharp drop in output at low state-of-charge (SOC) levels (e.g., below 30%). This restricts their use in fields where output characteristics are particularly critical, such as electric vehicles. Furthermore, high-nickel cathode active materials exhibit low stability. When lithium-ion batteries operate under high voltage or high temperature conditions, structural degradation may occur due to structural instability during charging and discharging. Side reactions with the electrolyte can also lead to degradation of the electrode surface structure or the film formed on the positive and / or negative electrode surfaces, while transition metal ions may dissolve from the positive electrode surface. As described above, the dissolved transition metal ions degrade the passivation capability of the solid electrolyte interphase (SEI) while depositing on the negative electrode, thus causing negative electrode degradation.

[0007] Recently, in order to solve this problem, a method has been proposed to replace high-nickel cathode active materials with olivine-structured lithium iron phosphate, which has excellent high-temperature safety.

[0008] However, since lithium iron phosphate has a lower theoretical capacity than conventionally used high-nickel cathode active materials, its disadvantage is that, when designing electrodes under the same conditions, its energy density is relatively lower than that of high-nickel cathode active materials.

[0009] Therefore, in order to solve this problem, high-load electrodes that increase the coating amount (loading) of electrode active material per unit area when using lithium iron phosphate have recently been explored.

[0010] However, because high-load electrodes not only have a high degree of active material coating but are also designed to increase electrode density, the degree of electrode compression is very large. This results in a drawback: insufficient porous structure in the electrode leads to reduced electrolyte impregnation. If electrolyte impregnation is reduced as described above, the "charge transfer" that occurs between lithium ions and electrons decreases, potentially increasing battery resistance and thus reducing the battery's capacity characteristics.

[0011] Therefore, there is a need to develop a new type of secondary battery that can improve electrolyte impregnation during the fabrication of secondary batteries using high-load electrodes, while simultaneously improving charge mobility. Summary of the Invention

[0012] [Technical Issues]

[0013] One aspect of the present invention provides a lithium secondary battery in which, when using a high-load positive electrode, the electrolyte impregnation is improved by using an electrolyte in which the amount of a specific electrolyte additive is controlled according to the load of the positive electrode, and a stable film is formed on the surface of the electrode to enhance charge transfer. Therefore, the increase in resistance during high-temperature storage can be suppressed and excellent cycle capacity retention can be ensured.

[0014] [Technical Solution]

[0015] [1] The present invention provides a lithium secondary battery comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode comprises lithium iron phosphate as a positive electrode active material, and the electrolyte comprises a lithium salt, a first organic solvent, a second organic solvent and an additive, wherein the first organic solvent is a cyclic lactone compound, the second organic solvent is a carbonate organic solvent, the additive is lithium nitrate (LiNO3), and satisfies the following relationship 1.

[0016] [Relation 1]

[0017]

[0018] In relation 1,

[0019] A represents the total amount (g) of electrolyte injected into the lithium secondary battery.

[0020] B represents the amount (% by weight) of lithium nitrate (LiNO3) contained in the injected electrolyte,

[0021] C is the loading amount of the positive electrode (g / cm 2 ), and

[0022] D is the total surface area of the positive electrode current collector (cm 2 ).

[0023] [2] The present invention provides the lithium secondary battery according to the above [1], wherein the lithium iron phosphate comprises a compound represented by Formula 1:

[0024] [Formula 1]

[0025] Li 1+a Fe x M y (PO 4-b )X' b

[0026] In [Formula 1], M is any one selected from the group consisting of aluminum (Al), magnesium (Mg), nickel (Ni), cobalt (Co), manganese (Mn), titanium (Ti), gallium (Ga), copper (Cu), vanadium (V), niobium (Nb), zirconium (Zr), cerium (Ce), indium (In), zinc (Zn) and yttrium (Y), X' is at least one element selected from the group consisting of fluorine (F), sulfur (S) and nitrogen (N), and -0.5≤a≤0.5, 0<x≤1, 0≤y≤1 and 0≤b≤0.3.

[0027] [3] The present invention provides the lithium secondary battery according to the above [1] or [2], wherein the lithium iron phosphate is lithium iron phosphate (LiFePO4) or lithium manganese iron phosphate (LiFeMnPO4).

[0028] [4] The present invention provides the lithium secondary battery according to at least one of the above [1] to [3], wherein the cyclic lactone compound comprises γ-butyrolactone.

[0029] [5] The present invention provides the lithium secondary battery according to at least one of the above [1] to [4], wherein the carbonate-based organic solvent is a cyclic carbonate-based organic solvent.

[0030] [6] The present invention provides the lithium secondary battery according to at least one of the above [1] to [5], wherein the first organic solvent and the second organic solvent are present in a volume ratio of 50:50 to 99:1.

[0031] [7] The present invention provides the lithium secondary battery according to at least one of the above [1] to [6], wherein in Relational Expression 1, A is from 3.0 g to 8.5 g.

[0032] [8] The present invention provides a lithium secondary battery of at least one of [1] to [7] above, wherein, in formula 1, C is 0.032 g / cm³. 2 Up to 0.064 g / cm 2 .

[0033] [9] The present invention provides a lithium secondary battery of at least one of [1] to [8] above, wherein, in relation 1, D is 310 cm. 2 Up to 450 cm 2 .

[0034]

[10] The present invention provides a lithium secondary battery of at least one of [1] to [9] above, wherein the negative electrode comprises a carbon-based active material, a silicon-based active material, or a mixture of a carbon-based active material and a silicon-based active material.

[0035]

[11] The present invention provides a lithium secondary battery of at least one of [1] to

[10] above, wherein the capacity of the lithium secondary battery is from 1,000 mAh to 3,000 mAh.

[0036] [Beneficial Effects]

[0037] Because the electrolyte used in the lithium secondary battery of the present invention includes an organic solvent containing a cyclic lactone compound as the main solvent and lithium nitrate (LiNO3) as an additive in an amount controlled according to the loading of the positive electrode, the electrolyte impregnation of the high-load positive electrode can be improved, and a film with low resistance can be formed on the surface of the high-load positive electrode, thereby improving the charge mobility on the surface of the high-load positive electrode. Therefore, the cycle characteristics and high-temperature storage characteristics of the lithium secondary battery of the present invention can be improved. Detailed Implementation

[0038] It will be understood that the words or terms used in the specification and claims should not be interpreted as having the meaning defined in a common dictionary, and it will be further understood that, based on the principle that the inventors may appropriately define the meaning of words or terms to best interpret the invention, the words or terms should be interpreted as having a meaning consistent with their meaning in the context of the related art and in the technical concept of the invention.

[0039] For example, it will be further understood that the terms “comprising,” “including,” or “having” in this specification specify the presence of the stated features, figures, steps, elements, or combinations thereof, but do not exclude the presence or addition of one or more other features, figures, steps, elements, or combinations thereof.

[0040] Furthermore, in the description of "a to b carbon atoms" in this specification, "a" and "b" each represent the number of carbon atoms contained in a specific functional group. That is, a functional group can contain "a" to "b" carbon atoms. For example, the description "alkylene with 1 to 5 carbon atoms" means an alkylene containing 1 to 5 carbon atoms, namely, -CH2-, -CH2CH2-, -CH2CH2CH2-, -CH2(CH2)CH-, -CH2CH2CH2CH2CH2-, and -CH(CH2)CH2CH2-.

[0041] Furthermore, in this specification, the term "alkylene" refers to a branched or unbranched aliphatic hydrocarbon group or a functional group having a hydrogen atom removed from the carbon atoms at both ends of an aliphatic hydrocarbon group. In one embodiment, the alkylene group may or may not have substituents. Alkylenes may include, but are not limited to, methylene, ethylene, propylene, isopropylene, butylene, isobutylene, tert-butylene, pentylene, and 3-pentylene, and in another embodiment, each may optionally have substituents.

[0042] Furthermore, unless otherwise defined in the specification, the expression “substitution” means that at least one hydrogen atom bonded to carbon is replaced by another element (e.g., fluorine).

[0043] Furthermore, the term "loading" in this specification refers to the amount of active material per unit area of ​​the positive electrode active material layer containing lithium iron phosphate formed on the current collector, expressed as "g / cm²". 2 In this case, "the load on the positive electrode" in this specification refers to the sum of the loads on the two surfaces of the positive electrode.

[0044] The present invention will be described in detail below.

[0045] The lithium secondary battery of the present invention includes at least one of the configurations disclosed below, and may include any combination of technically possible configurations among the following configurations.

[0046] Lithium secondary batteries

[0047] This invention relates to a lithium secondary battery.

[0048] Specifically, the present invention provides a lithium secondary battery comprising a positive electrode, a negative electrode, and an electrolyte.

[0049] The positive electrode can include lithium iron phosphate as the positive electrode active material.

[0050] Electrolytes may include lithium salts, a first organic solvent, a second organic solvent, and additives.

[0051] The first organic solvent may include cyclic lactone compounds.

[0052] The second organic solvent may include a carbonate-based organic solvent.

[0053] The additive is lithium nitrate (LiNO3) and satisfies the following relational expression 1.

[0054] [Relational Expression 1]

[0055]

[0056] In Relational Expression 1,

[0057] A is the total mass (g) of electrolyte injected into the lithium secondary battery,

[0058] B is the mass percentage of lithium nitrate (LiNO3) contained in the injected electrolyte,

[0059] C is the loading capacity of the positive electrode (g / cm 2 ), and

[0060] D is the total area of the surface of the positive electrode current collector (cm 2 ).

[0061] Hereinafter, each component of the lithium secondary battery of the present invention will be described in detail.

[0062] (1) Positive Electrode

[0063] The positive electrode of the present invention may include lithium iron phosphate as a positive active material, and the lithium iron phosphate may be represented by the following formula 1.

[0064] [Formula 1]

[0065] Li 1+a Fe x M y (PO 4-b )X' b

[0066] In [Formula 1],

[0067] M is any one selected from the group consisting of aluminum (Al), magnesium (Mg), nickel (Ni), cobalt (Co), manganese (Mn), titanium (Ti), gallium (Ga), copper (Cu), vanadium (V), niobium (Nb), zirconium (Zr), cerium (Ce), indium (In), zinc (Zn) and yttrium (Y),

[0068] X' is at least one element selected from the group consisting of fluorine (F), sulfur (S) and nitrogen (N), and

[0069] -0.5≤a≤0.5, 0<x≤1, 0≤y≤1 and 0≤b≤0.3.

[0070] As a representative example, the lithium iron phosphate represented by Formula 1 may include lithium iron phosphate (LiFePO4, LFP) or lithium manganese iron phosphate (LiFeMnPO4, LFMP).

[0071] As a lithium iron phosphate represented by Formula 1, primary particles with nanoscale dimensions can be used for high lithium ion input / output. Secondary particles, which are aggregates of primary particles, can also be prepared by assembling these primary particles. For example, when using primary particles as lithium iron phosphate, the particle size can be from 50 nm to 2,000 nm, more specifically from 200 nm to 1,100 nm. Furthermore, when secondary particles, which are aggregates of primary particles, are prepared by assembling these primary particles and used, the average particle size (D50) of the secondary particles can be from 0.5 μm to 30 μm.

[0072] The lithium iron phosphate represented by Formula 1 maintains structural and thermal stability even during volume changes caused by charging and discharging because phosphorus and oxygen form strong covalent bonds in the tetrahedral structure of PO4. Furthermore, the lithium iron phosphate represented by Formula 1 can be coated with an amorphous layer of carbon or metal oxide on its surface. In this case, since the amorphous layer of carbon or metal oxide coated on the surface is not crystalline, lithium ions can penetrate through this amorphous shell to insert into / extract from the lithium iron phosphate core. Because the amorphous layer of carbon or metal oxide coated on the surface has excellent electronic conductivity while allowing lithium ions to pass through, it can also act as a current path to the lithium iron phosphate core, which is the active material, thus enabling high-rate charging and discharging. Moreover, when the surface of the lithium iron phosphate is coated with an amorphous layer of carbon or metal oxide, unnecessary reactions between the core material and the electrolyte solution can be controlled, thereby further improving safety.

[0073] To design the high-capacity electrode of this invention, the positive electrode loading can be 0.032 g / cm³. 2 The above (based on the loading of a single-sided positive electrode: 0.016 g / cm³) 2 (Above), specifically, it can be 0.032 g / cm³. 2 Up to 0.064 g / cm 2 More preferably, it can be 0.040 g / cm³. 2 Up to 0.060 g / cm 2 When the loading of the positive electrode active material meets the above range, a high energy density battery can be designed.

[0074] The positive electrode of the present invention may include a positive electrode current collector; and a positive electrode material mixture layer disposed on at least one surface of the positive electrode current collector. In this case, the positive electrode material mixture layer may include the aforementioned lithium iron phosphate as the positive electrode active material.

[0075] Positive current collectors can typically have a thickness ranging from 3 μm to 500 μm.

[0076] Microscopic irregularities can be formed on the surface of the positive electrode current collector to improve the adhesion of the positive electrode active material. For example, the positive electrode current collector can be used in various shapes, such as membranes, sheets, foils, meshes, porous bodies, foams, and nonwoven fabrics.

[0077] A positive electrode material mixture layer is disposed on at least one surface of the positive electrode current collector. Specifically, the positive electrode material mixture layer may be disposed on one or both surfaces of the positive electrode current collector.

[0078] Moreover, considering that it exhibits sufficient capacity, the lithium iron phosphate represented by Formula 1 can be included in the cathode material mixture layer in an amount of 80% to 99% by weight.

[0079] Furthermore, the porosity of the cathode material mixture layer, as measured by the Brunauer-Emmett-Teller (BET) method, can be 20% to 40%, and specifically 20% to 30%.

[0080] When the porosity of the cathode material mixture layer meets the above-mentioned range, the interfacial resistance of the cathode can be reduced, and a high-density electrode can be obtained, thereby improving the output characteristics of the battery.

[0081] The positive electrode material mixture layer may also include a binder and / or a conductive agent together with the aforementioned positive electrode active material.

[0082] Adhesives enhance the adhesion between positive electrode active material particles and between the positive electrode active material and the current collector. Examples of adhesives include any one or a mixture of two or more of the following: fluoropolymer adhesives, such as polyvinylidene fluoride (PVDF); rubber adhesives, including styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber, or styrene-isoprene rubber; cellulose adhesives, including carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, or regenerated cellulose; polyol adhesives, including polyvinyl alcohol; polyolefin adhesives, including polyethylene or polypropylene; polyimide adhesives; polyester adhesives; and silane adhesives.

[0083] The adhesive may be included in the cathode material mixture layer in an amount of 0.1% to 15% by weight, preferably 0.1% to 10% by weight.

[0084] Next, a conductive agent is used to provide conductivity to the electrode. Any conductive agent can be used without particular limitation, as long as it is electronically conductive and does not cause chemical changes in the battery. Specific examples of conductive agents include: carbon black, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, or thermally cracked carbon black; graphite powder, such as natural graphite, artificial graphite, or graphite with a highly developed crystal structure; conductive fibers, such as carbon fibers or metal fibers; conductive powders, such as fluorocarbon powders, aluminum powder, and nickel powder; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or polyphenylene derivatives.

[0085] The conductive agent can be added to the positive electrode material mixture layer in amounts ranging from 1% to 30% by weight.

[0086] The positive electrode can be prepared by coating a positive electrode current collector with a positive electrode slurry comprising a positive electrode active material and optionally a binder, a conductive agent, and a positive electrode slurry forming solvent, followed by drying and rolling the coated positive electrode current collector. Alternatively, the positive electrode can be prepared by mixing the positive electrode active material with optional binders and conductive agents to prepare a membrane, and then laminating the membrane onto the positive electrode current collector.

[0087] The porosity of the cathode material mixture layer measured by the BET method after rolling can be 20% to 40%, and specifically 20% to 30%.

[0088] In promoting the dispersion of the positive electrode active material, binder and / or conductive agent, the solvent for forming the positive electrode slurry may include, for example, at least one selected from distilled water, N-methylpyrrolidone, ethanol, methanol or isopropanol, and preferably may include N-methylpyrrolidone.

[0089] (2) Negative electrode

[0090] Next, the negative electrode will be described.

[0091] The negative electrode may include a negative electrode active material.

[0092] As a negative electrode active material, carbon-based active materials, silicon-based active materials, or a mixture of carbon-based and silicon-based active materials can be used.

[0093] As carbon-based active materials, various carbon-based active materials used in the art can be used, such as graphite-based materials, such as natural graphite, artificial graphite, and Kish graphite; pyrolytic carbon, mesophase pitch-based carbon fibers, mesophase carbon microspheres, mesophase pitch, high-temperature sintered carbon (e.g., coke derived from petroleum or coal tar pitch), soft carbon, and hard carbon. There are no particular limitations on the shape of the carbon-based active material, and materials of various shapes can be used, such as irregular shapes, plates, sheets, spheres, or fibers.

[0094] Specifically, as the carbon-based active material, any one of natural graphite or artificial graphite can be used, and natural graphite and artificial graphite can be used in combination to inhibit peeling of the active material by improving adhesion to the current collector.

[0095] Furthermore, the silicon-based active material may for example include a material selected from the group consisting of elemental silicon (Si), silicon oxide (SiO x , wherein 0 < x < 2), silicon carbide (SiC) or Si-Y alloy (wherein Y is an element selected from alkali metals, alkaline earth metals, group 13 elements, group 14 elements, transition metals, rare earth elements, or combinations thereof, and is not Si). Element Y may be selected from the group consisting of Mg, calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), scandium (Sc), Y, Ti, Zr, hafnium (Hf), Rf, V, Nb, tantalum (Ta), Db, chromium (Cr), molybdenum (Mo), tungsten (W), Sg, technetium (Tc), rhenium (Re), Bh, iron (Fe), lead (Pb), ruthenium (Ru), osmium (Os), Hs, rhodium (Rh), iridium (Ir), palladium (Pd), platinum (Pt), Cu, silver (Ag), gold (Au), Zn, cadmium (Cd), boron (B), Al, Ga, tin (Sn), In, Ti, germanium (Ge), phosphorus (P), arsenic (As), antimony (Sb), bismuth (Bi), S, selenium (Se), tellurium (Te), polonium (Po), and combinations thereof.

[0096] In terms of ensuring structural stability during charging and discharging and reducing side reactions with the electrolyte solution, the average particle size (D 50 ) of the silicon-based active material can be 1 μm to 30 μm, preferably 2 μm to 15 μm.

[0097] Furthermore, the negative electrode of the present invention may comprise at least one selected from carbon-based active materials and silicon-based active materials.

[0098] Specifically, the negative electrode of the present invention may comprise a carbon-based active material and a silicon-based active material.

[0099] In this case, the weight ratio of the silicon-based active material to the carbon-based active material can be 1:99 to 30:70, specifically 3:97 to 15:85. When the mixing ratio of the silicon-based active material and the carbon-based active material satisfies the above range, excellent cycling performance can be ensured because volume expansion of the silicon-based active material is inhibited while capacity characteristics are improved.

[0100] The negative electrode may comprise a negative electrode current collector; and a negative electrode material mixture layer disposed on at least one surface of the negative electrode current collector. In this case, the negative electrode active material may be comprised in the negative electrode material mixture layer.

[0101] There are no particular restrictions on the negative electrode current collector, as long as it has high conductivity and does not cause chemical changes in the battery. Specifically, as a negative electrode current collector, copper, stainless steel, aluminum, nickel, titanium, sintered carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium or silver, and aluminum-cadmium alloys can be used.

[0102] Negative current collectors can typically have a thickness ranging from 3 μm to 500 μm.

[0103] Microscopic irregularities can be formed on the surface of the negative electrode current collector to improve the adhesion of the negative electrode active material. For example, the negative electrode current collector can be used in various shapes, such as membranes, sheets, foils, meshes, porous bodies, foams, and nonwoven fabrics.

[0104] The negative electrode material mixture layer is disposed on at least one surface of the negative electrode current collector. Specifically, the negative electrode material mixture layer may be disposed on one or both surfaces of the negative electrode current collector.

[0105] In order to fully realize the capacity of the secondary battery while minimizing the impact of volume expansion / contraction on the battery, the negative electrode active material can be included in the negative electrode material mixture layer in an amount of 60% to 99% by weight.

[0106] Moreover, the porosity of the anode material mixture layer measured by the BET method can be 20% to 40%, and specifically 20% to 30%.

[0107] When the porosity of the negative electrode material mixture layer meets the above-mentioned range, the interfacial resistance of the negative electrode can be reduced, thereby improving the output characteristics of the battery.

[0108] The negative electrode material mixture layer may also include a conductive agent and / or binder together with the negative electrode active material.

[0109] Conductive agents are components used to further improve the conductivity of negative electrode active materials. There are no particular restrictions on them, as long as they are conductive and do not cause chemical changes in the battery. For example, the following conductive materials can be used: carbon black, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, or thermally cracked carbon black; graphite powder, such as natural graphite, artificial graphite, or graphite with a highly developed crystal structure; conductive fibers, such as carbon fibers or metal fibers; conductive powders, such as fluorocarbon powders, aluminum powder, and nickel powder; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or polyphenylene derivatives.

[0110] The conductive agent can be added to the negative electrode material mixture layer in an amount of less than 10% by weight, preferably less than 5% by weight.

[0111] Adhesives are components that facilitate bonding between conductive agents, active materials, and current collectors. Adhesives typically include: fluoropolymer adhesives, such as polyvinylidene fluoride (PVDF); rubber adhesives, including styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber, or styrene-isoprene rubber; cellulose adhesives, including carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, or regenerated cellulose; polyol adhesives, including polyvinyl alcohol; polyolefin adhesives, including polyethylene or polypropylene; polyimide adhesives; polyester adhesives; and silane adhesives.

[0112] The adhesive may be included in the negative electrode material mixture layer in an amount of 0.1% to 15% by weight, preferably 0.1% to 10% by weight.

[0113] The negative electrode can be prepared by coating a negative electrode current collector with a negative electrode slurry comprising a negative electrode active material and optionally a binder, a conductive agent, and a negative electrode slurry, followed by drying and rolling the coated negative electrode current collector. Alternatively, the negative electrode can be prepared by mixing a negative electrode active material with optional binders and conductive agents to prepare a membrane, and then laminating the membrane onto the negative electrode current collector.

[0114] The porosity of the negative electrode material mixture layer after rolling, as measured by the BET method, can be 20% to 40%, and specifically 20% to 30%.

[0115] In promoting the dispersion of the negative electrode active material, binder and / or conductive agent, the solvent for forming the negative electrode slurry may include, for example, at least one selected from distilled water, N-methylpyrrolidone, ethanol, methanol or isopropanol, and preferably may include distilled water.

[0116] (3) Diaphragm

[0117] The separator separates the negative and positive electrodes and provides a path for the movement of lithium ions. Any separator can be used without particular limitation, as long as it is commonly used in lithium secondary batteries. In particular, separators with high moisture retention capacity for non-aqueous electrolytes and low resistance to the transfer of non-aqueous electrolyte ions can be used.

[0118] Specifically, as the separator, porous polymer membranes can be used, such as porous polymer membranes prepared from polyolefin polymers (e.g., ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers, and ethylene / methacrylate copolymers), or laminates of two or more layers thereof. Alternatively, typical porous nonwoven fabrics can be used, such as nonwoven fabrics formed from high-melting-point glass fibers or polyethylene terephthalate fibers. Furthermore, coated separators containing ceramic components or polymer materials can be used to ensure heat resistance or mechanical strength, and separators with single-layer or multi-layer structures can be optionally used.

[0119] (4) Electrolytes

[0120] Next, the electrolyte of the present invention may include: lithium salt; a first organic solvent; a second organic solvent; and additives, and specific examples of each component are described below.

[0121] (4-1) Lithium salts

[0122] First, as the lithium salt, there are no restrictions on the use of lithium salts commonly used in electrolytes for lithium secondary batteries. For example, the lithium salt can contain Li. + As a cation, and may contain a selection from F - Cl - ,Br - I - N(CN)2 - BF4 - ClO4 - B 10 Cl 10 - AlCl4 - AlO2 - PF6 - CF3SO3 - CH3CO2 - CF3CO2 - AsF6 - SbF6 - CH3SO3 - (CF3CF2SO2)2N - (CF3SO2)2N - (FSO2)2N - BF2C2O4 - BC4O8 - PF4C2O4 - PF2C4O8 - (CF3)2PF4 - (CF3)3PF3 - (CF3)4PF2 -(CF3)5PF - (CF3)6P - C4F9SO3 - CF3CF2SO3 - CF3CF2(CF3)2CO - (CF3SO2)2CH - CF3(CF2)7SO3 - or SCN - Any one of them can be used as an anion.

[0123] Specifically, lithium salts may include those selected from LiCl, LiBr, LiI, LiBF4, LiClO4, and LiB. 10 Cl 10 The material may include one or more of the following: LiAlCl4, LiAlO2, LiPF6, LiCF3SO3, LiCH3CO2, LiCF3CO2, LiAsF6, LiSbF6, LiCH3SO3, LiN(SO2F)2 (lithium bis(fluorosulfonyl)imide, LiFSI), LiN(SO2CF2CF3)2 (lithium bis(pentafluoroethanesulfonyl)imide, LiBETI), or LiN(SO2CF3)2 (lithium bis(trifluoromethanesulfonyl)imide, LiTFSI), and specifically may include at least one of the following: LiBF4, LiPF6, LiN(SO2F)2 (lithium bis(fluorosulfonyl)imide, LiFSI), LiN(SO2CF2CF3)2 (lithium bis(pentafluoroethanesulfonyl)imide, LiBETI), or LiN(SO2CF3)2 (lithium bis(trifluoromethanesulfonyl)imide, LiTFSI). In addition to these materials, lithium salts commonly used in electrolytes for lithium secondary batteries can also be used without limitation.

[0124] The lithium salt can be appropriately varied within the generally available range, but it can be included in the electrolyte at a concentration of 0.8 M to 3.0 M, specifically 1.0 M to 2.0 M, preferably 1.0 M to 1.8 M, to achieve the best effect of forming an anti-corrosion film on the electrode surface.

[0125] When the concentration of lithium salt is within the above range, the viscosity of the electrolyte can be controlled to achieve optimal impregnation, and the capacity and cycle characteristics of lithium secondary batteries can be improved by increasing the mobility of lithium ions.

[0126] (4-2) First organic solvent

[0127] Next, the first organic solvent will be described.

[0128] The first organic solvent may include cyclic lactone compounds.

[0129] Cyclic lactone compounds are compounds with high dielectric constants and ionic conductivity, which can improve charge transfer degradation that occurs when operating under high load electrodes.

[0130] Cyclic lactone compounds can include γ-butyrolactone.

[0131] Based on the total weight of the electrolyte, the content of the first organic solvent may be from 39% to 80% by weight, specifically from 48% to 80% by weight, more preferably from 52% to 70% by weight.

[0132] When the amount of the first organic solvent in this invention meets the above-mentioned range, the effect of reducing battery resistance can be achieved by improving lithium-ion transfer characteristics.

[0133] (4-3) Second organic solvent

[0134] Next, the second organic solvent will be described.

[0135] The second organic solvent may include carbonate organic solvents, which can minimize decomposition caused by oxidation reactions during the charging and discharging of the secondary battery and can exhibit the desired performance together with additives.

[0136] Specifically, the carbonate organic solvent preferably includes any one of cyclic carbonate organic solvents having high ionic conductivity and high dielectric constant or linear carbonate organic solvents having low viscosity and low dielectric constant, and may specifically include cyclic carbonate organic solvents.

[0137] Specifically, cyclic carbonate organic solvents may include any one or more of the following organic solvents selected from ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentene carbonate, 2,3-pentene carbonate, vinylene carbonate, or fluoroethylene carbonate (FEC), and wherein the cyclic carbonate organic solvents may include ethylene carbonate capable of maintaining the stable passivation capability of the solid electrolyte interphase (SEI) layer.

[0138] Linear carbonate organic solvents may include any one or more of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate, or ethyl propyl carbonate, and wherein the linear carbonate organic solvent may include dimethyl carbonate (DMC) which has low viscosity and small molecular size among linear carbonate organic solvents.

[0139] Specifically, the second organic solvent can be ethylene carbonate, propylene carbonate, or a mixture thereof.

[0140] When cyclic carbonates and linear carbonates are mixed and used as a second organic solvent, in order to ensure low viscosity characteristics, the cyclic carbonate organic solvent and the linear carbonate organic solvent can be mixed in a volume ratio of about 1:99 to 50:50 or 20:80 to 40:60.

[0141] If necessary, the electrolyte of the present invention may additionally contain a linear ester organic solvent as a third organic solvent.

[0142] As a representative example, linear ester organic solvents may include at least one organic solvent selected from methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate or butyl propionate, and specifically may include at least one of methyl acetate and ethyl acetate.

[0143] In the electrolyte of the present invention, the first organic solvent and the second organic solvent may be contained in a volume ratio of 50:50 to 99:1, and specifically in a volume ratio of 70:30 to 99:1.

[0144] When the mixing ratio of the first organic solvent to the second organic solvent meets the above-mentioned range, a high ion transfer characteristic effect can be achieved, and battery performance with low resistance characteristics can be ensured. That is, when the volume ratio of the first organic solvent is 50 or more, the ion transfer characteristic effect can be ensured, and when the volume ratio is 99 or less, a stable film can be formed to improve battery life characteristics.

[0145] (4-4) Additives

[0146] Furthermore, the electrolyte of the present invention may include lithium nitrate (LiNO3) as an additive.

[0147] Lithium nitrate (LiNO3), as an additive, can form an inorganic film comprising lithium-nitrogen and lithium-oxygen bonds on the negative electrode surface during the formation step. Since this inorganic film increases surface energy and acts as an ion transporter capable of uniformly transporting lithium ions, it can improve the electrolyte's impregnation of the electrode and induce more efficient charge transfer reactions.

[0148] Furthermore, since lithium nitrate (LiNO3), which is included as an additive, can form coordination bonds with transition metals dissolved from the positive electrode at high temperatures, or with Lewis acids produced by the decomposition products of lithium salts, it can suppress the electrodeposition of transition metal ions on the negative electrode surface, thereby preventing reversible lithium loss and thus improving the degradation of cycle characteristics.

[0149] The amount (by weight%) of lithium nitrate (LiNO3) as an additive can vary depending on the loading of the cathode, and preferably satisfies the following relationship 1.

[0150] [Relation 1]

[0151]

[0152] In relation 1,

[0153] A represents the total amount (g) of electrolyte injected into the lithium secondary battery.

[0154] B represents the amount (by weight%) of lithium nitrate (LiNO3) contained in the injected electrolyte.

[0155] C represents the loading of the positive electrode (g / cm³). 2 ),and

[0156] D is the total surface area of ​​the positive electrode current collector (cm²). 2 ).

[0157] Specifically, in Equation 1, A can be from 3.0 g to 8.5 g. When A is above 3.0 g, the impregnation of the electrolyte to the electrode assembly can be easily controlled, and when A is below 8.5 g, the impregnation of the electrolyte and the prevention of increased battery thickness can be improved by controlling the amount of gas generated in the cell during battery operation.

[0158] Furthermore, in order to design high-capacity electrodes, C can be 0.032 g / cm³ in Equation 1. 2 Up to 0.064 g / cm 2 .

[0159] Furthermore, in Equation 1, D represents the total area of ​​the two surfaces of the positive electrode current collector coated with the positive electrode active material, which can specifically be 310 cm². 2 Up to 450 cm 2 This allows it to be used in small batteries.

[0160] 0.02 is a constant that is determined by multiplying 0.01 (a decimal value used to express the percentage of the amount of additives in the electrolyte) by 2 (an integer value used to convert the positive electrode loading of C to the one-sided loading).

[0161] When the amount (by weight%) of lithium nitrate (LiNO3) used as an additive in the electrolyte of the present invention satisfies Formula 1, excellent battery performance can be ensured because the electrolyte impregnation of the electrode can be improved and an inorganic film including lithium-nitrogen and lithium-oxygen bonds that can improve ion transfer characteristics can be uniformly formed on the surface of the negative electrode. That is, when the value of Formula 1 is 0.0001 or more, or 0.0005 or more, preferably 0.001 or more, the uniform formation of a film that can act as an effective ion transporter instead of a resistor to suppress the increase in battery resistance can prevent the occurrence of battery performance degradation and can prevent the degradation of lifetime performance at low temperatures (below zero temperature). Moreover, when the value of Formula 1 is 0.050 or less, or 0.040 or less, preferably 0.030 or less, the generation of unnecessary activation gases can be prevented by suppressing side reactions, thus preventing the degradation of high-temperature cycling and high-temperature storage characteristics.

[0162] (4-5) Other additives

[0163] If necessary, the lithium secondary battery of the present invention may further include other additives in the electrolyte to prevent negative electrode collapse caused by electrolyte decomposition under high output conditions, or to further improve low-temperature high-rate discharge characteristics, high-temperature stability, overcharge protection, and the effect of suppressing battery expansion at high temperatures. When the electrolyte of the present invention also includes other additives, lithium nitrate (LiNO3) can be referred to as the first additive, and the other additives can be referred to as the second additive.

[0164] Typical examples of other additives may include any one of the following: cyclic carbonates, sulfates / salts, sulfonyl lactones, phosphates / salts, borates / salts, nitriles, benzenes, amines, silanes, or lithium salts.

[0165] Specifically, cyclic carbonate compounds can include vinylene carbonate (VC).

[0166] Sulfate / salt compounds may include ethylene sulfate (Esa), trimethylol sulfate (TMS), or methyltrimethylol sulfate (MTMS).

[0167] Sulfolactone compounds may include any one of the following compounds: 1,3-propanesulfonyl lactone (PS), 1,4-butanesulfonyl lactone, ethanesulfonyl lactone, 1,3-propenesulfonyl lactone (PRS), 1,4-butenesulfonyl lactone, or 1-methyl-1,3-propenesulfonyl lactone.

[0168] Phosphate ester / salt compounds may include at least one compound selected from lithium difluoro(bis(oxalato)phosphate), lithium difluorophosphate, tris(trimethylsilyl)phosphate, tris(2,2,2-trifluoroethyl)phosphate, or tris(trifluoroethyl)phosphate.

[0169] Boronate / salt compounds may include tetraphenylborate and lithium oxaloyl difluoroborate.

[0170] Nitrile compounds may include any one of the following: butadionitrile, adiponitrile, acetonitrile, propionitrile, butadionitrile, valerate, octanoic acid, heptanoic acid, cyclopentaneformitrile, cyclohexaneformitrile, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, phenylacetonitrile, 2-fluorophenylacetonitrile, or 4-fluorophenylacetonitrile.

[0171] Benzene compounds may include fluorobenzene, amine compounds may include triethanolamine or ethylenediamine, and silane compounds may include tetravinylsilane.

[0172] Lithium salt compounds are compounds that are different from lithium salts contained in electrolytes, and may include at least one compound selected from LiPO2F2, LiODFB, LiBOB (lithium bis(oxalato)borate (LiB(C2O4)2), LiBF4 or LiDFOP).

[0173] Two or more other additives may be mixed and used, and the content of other additives may be less than 10% by weight, particularly from 0.01% to less than 8.0% by weight, preferably from 0.05% to 5.0% by weight, based on the total weight of the electrolyte.

[0174] Preferably, in the electrolyte of the present invention, lithium nitrate (LiNO3) and other additives may be included in a weight ratio of 1:0.01 to 1:50, in a weight ratio of 1:0.1 to 1:10, and more preferably in a weight ratio of 1:0.1 to 1:6.

[0175] When the electrolyte of the present invention includes additives within the above-mentioned range and other additives, a stable film can be formed simultaneously on the surfaces of both the positive and negative electrodes. That is, when other additives are present in a weight ratio of 50 or less, a uniform film can be formed on the surface of the negative electrode to prevent it from acting as a resistive element, and since the electrodeposition of metal materials on the negative electrode can be suppressed by inhibiting the dissolution of transition metals, an increase in film thickness and resistance can be prevented. When a relatively large amount of other additives is included, the film thickness increases due to the increased amount of other additives that decompose and reductively react on the negative electrode surface. Therefore, the additives cannot function effectively and instead act as resistive elements, potentially leading to a significant reduction in cell performance.

[0176] The shape of the lithium secondary battery of the present invention is not particularly limited, but cylindrical, prismatic, pouch or coin-shaped batteries can be used.

[0177] Furthermore, the lithium secondary battery of the present invention can be used in portable devices, such as mobile phones, laptops and digital cameras, as well as electric vehicles, such as hybrid electric vehicles (HEVs).

[0178] Furthermore, the lithium secondary battery of the present invention can be used not only as a single cell for powering small devices, but also as a unit cell in medium to large battery modules comprising multiple single cells. Specifically, the lithium secondary battery of the present invention can be used as a single cell for small devices with a capacity of 1,000 mAh to 3,000 mAh and a volume of width (33 mm to 39 mm) × length (80 mm to 96 mm) × thickness (3.0 mm to 5.0 mm).

[0179] The invention will now be described in detail with reference to specific embodiments. However, the invention may be embodied in many different forms and should not be construed as limited to the embodiments set forth herein. Rather, these exemplary embodiments are provided so that this specification will be thorough and complete, and will fully convey the scope of the invention to those skilled in the art.

[0180] [Example]

[0181] Example 1.

[0182] (Positive electrode preparation)

[0183] A positive electrode active material (LiFePO4), a conductive agent (carbon black), and a binder (polyvinylidene fluoride, PVDF) were added to N-methyl-2-pyrrolidone (NMP) as a solvent in a weight ratio of 96:1:3 to prepare a positive electrode active material slurry (67% by weight solids). This positive electrode active material slurry was then used to coat a 15 μm thick positive electrode current collector (Al film; total surface area of ​​the positive electrode current collector: 435 cm²). 2 The cathode was prepared by drying and rolling (cathode loading: 0.048 g / cm³). 2 Based on the loading capacity of the positive electrode single side: 0.024 g / cm³ 2 (Porosity of the cathode material mixture layer: 24%).

[0184] (Anode preparation)

[0185] A negative electrode active material (100% artificial graphite), CMC-SBR as a binder, and carbon black as a conductive agent were added to distilled water as a solvent in a weight ratio of 96:3.5:0.5 to prepare a negative electrode active material slurry (solid content 53 wt%). This negative electrode active material slurry was then coated onto an 8 μm thick negative electrode current collector (Cu film), dried, and rolled to prepare the negative electrode (porosity of the negative electrode material mixture layer: 26%).

[0186] (Electrolyte preparation)

[0187] LiPF6 was dissolved in an organic solvent in which γ-butyrolactone and ethylene carbonate were mixed in a volume ratio of 70:30 to make the concentration of LiPF6 1.0 M, and then 1.0 wt% of lithium nitrate (LiNO3) was added to prepare the electrolyte for lithium secondary batteries of the present invention.

[0188] (Preparation of secondary batteries)

[0189] Electrode assemblies were prepared by a conventional method in which the positive and negative electrodes prepared by the above method were stacked together with a polyethylene porous membrane. The assemblies were then housed in a pouch-type secondary battery casing, and 3.65 g of the electrolyte for lithium secondary batteries prepared above was injected to prepare a lithium secondary battery (see Table 1 below).

[0190] Example 2.

[0191] (Electrolyte preparation)

[0192] LiPF6 was dissolved in an organic solvent in which γ-butyrolactone and ethylene carbonate were mixed in a volume ratio of 70:30 to make the concentration of LiPF6 1.0 M, and then 1.0 wt% of lithium nitrate (LiNO3) was added to prepare the electrolyte for lithium secondary batteries of the present invention.

[0193] (Preparation of secondary batteries)

[0194] A lithium secondary battery was prepared in the same manner as in Example 1, except that 4.98 g of the electrolyte for lithium secondary batteries prepared above was injected (see Table 1 below).

[0195] Example 3.

[0196] (Electrolyte preparation)

[0197] LiPF6 was dissolved in an organic solvent in which γ-butyrolactone and ethylene carbonate were mixed in a volume ratio of 70:30 to make the concentration of LiPF6 1.0 M, and then 1.0 wt% of lithium nitrate (LiNO3) was added to prepare the electrolyte for lithium secondary batteries of the present invention.

[0198] (Preparation of secondary batteries)

[0199] A lithium secondary battery was prepared in the same manner as in Example 1, except that 6.64 g of the electrolyte for lithium secondary batteries prepared above was injected (see Table 1 below).

[0200] Example 4.

[0201] (Positive electrode preparation)

[0202] A positive electrode active material (LiFePO4), a conductive agent (carbon black), and a binder (polyvinylidene fluoride, PVDF) were added to N-methyl-2-pyrrolidone (NMP) as a solvent in a weight ratio of 96:1:3 to prepare a positive electrode active material slurry (67% by weight solids). This positive electrode active material slurry was then used to coat a 15 μm thick positive electrode current collector (Al film; total surface area of ​​the positive electrode current collector: 435 cm²). 2 The cathode was prepared by drying and rolling (cathode loading: 0.064 g / cm³). 2 Based on the loading capacity of the positive electrode single side: 0.032 g / cm³ 2 (Porosity of the cathode material mixture layer: 24%).

[0203] (Electrolyte preparation)

[0204] LiPF6 was dissolved in an organic solvent in which γ-butyrolactone and ethylene carbonate were mixed in a volume ratio of 70:30 to make the concentration of LiPF6 1.0 M, and then 1.0 wt% of lithium nitrate (LiNO3) was added to prepare the electrolyte for lithium secondary batteries of the present invention.

[0205] (Preparation of secondary batteries)

[0206] A lithium secondary battery was prepared in the same manner as in Example 1, except that the positive electrode prepared by the above method was used, and 4.65 g of the electrolyte for lithium secondary batteries prepared above was injected (see Table 1 below).

[0207] Example 5.

[0208] (Electrolyte preparation)

[0209] LiPF6 was dissolved in an organic solvent in which γ-butyrolactone and ethylene carbonate were mixed in a volume ratio of 70:30 to make the concentration of LiPF6 1.0 M, and then 1.0 wt% of lithium nitrate (LiNO3) was added to prepare the electrolyte for lithium secondary batteries of the present invention.

[0210] (Preparation of secondary batteries)

[0211] A lithium secondary battery was prepared in the same manner as in Example 4, except that 6.43 g of the electrolyte for lithium secondary batteries prepared above was injected (see Table 1 below).

[0212] Example 6.

[0213] (Electrolyte preparation)

[0214] LiPF6 was dissolved in an organic solvent in which γ-butyrolactone and ethylene carbonate were mixed in a volume ratio of 70:30 to make the concentration of LiPF6 1.0 M, and then 1.0 wt% of lithium nitrate (LiNO3) was added to prepare the electrolyte for lithium secondary batteries of the present invention.

[0215] (Preparation of secondary batteries)

[0216] A lithium secondary battery was prepared in the same manner as in Example 4, except that 8.45 g of the electrolyte for lithium secondary batteries prepared above was injected (see Table 1 below).

[0217] Example 7.

[0218] (Positive electrode preparation)

[0219] A positive electrode active material (LiFePO4), a conductive agent (carbon black), and a binder (polyvinylidene fluoride, PVDF) were added to N-methyl-2-pyrrolidone (NMP) as a solvent in a weight ratio of 96:1:3 to prepare a positive electrode active material slurry (67% by weight solids). This positive electrode active material slurry was then used to coat a 15 μm thick positive electrode current collector (Al film; total surface area of ​​the positive electrode current collector: 312 cm²). 2 The cathode was prepared by drying and rolling (cathode loading: 0.048 g / cm³). 2 Based on the loading capacity of the positive electrode single side: 0.024 g / cm³ 2 (Porosity of the cathode material mixture layer: 24%).

[0220] (Anode preparation)

[0221] A negative electrode active material (100% artificial graphite), CMC-SBR as a binder, and carbon black as a conductive agent were added to distilled water as a solvent in a weight ratio of 96:3.5:0.5 to prepare a negative electrode active material slurry (solid content 53 wt%). This negative electrode active material slurry was then coated onto an 8 μm thick negative electrode current collector (Cu film), dried, and rolled to prepare the negative electrode (porosity of the negative electrode material mixture layer: 26%).

[0222] (Electrolyte preparation)

[0223] LiPF6 was dissolved in an organic solvent in which γ-butyrolactone and ethylene carbonate were mixed in a volume ratio of 70:30 to make the concentration of LiPF6 1.0 M, and then 0.5% by weight of lithium nitrate (LiNO3) was added to prepare the electrolyte for lithium secondary batteries of the present invention.

[0224] (Preparation of secondary batteries)

[0225] Electrode assemblies were prepared by a conventional method in which the positive and negative electrodes prepared by the above method were stacked together with a polyethylene porous membrane. The assemblies were then housed in a pouch-type secondary battery casing, and 3.10 g of the electrolyte for lithium secondary batteries prepared above was injected to prepare a lithium secondary battery (see Table 1 below).

[0226] Example 8.

[0227] (Electrolyte preparation)

[0228] LiPF6 was dissolved in an organic solvent in which γ-butyrolactone and ethylene carbonate were mixed in a volume ratio of 70:30 to make the concentration of LiPF6 1.0 M, and then 0.5% by weight of lithium nitrate (LiNO3) was added to prepare the electrolyte for lithium secondary batteries of the present invention.

[0229] (Preparation of secondary batteries)

[0230] The lithium secondary battery was prepared in the same manner as in Example 7, except that 3.57 g of the electrolyte for lithium secondary batteries prepared above was injected (see Table 1 below).

[0231] Example 9.

[0232] (Electrolyte preparation)

[0233] LiPF6 was dissolved in an organic solvent in which γ-butyrolactone and ethylene carbonate were mixed in a volume ratio of 70:30 to make the concentration of LiPF6 1.0 M, and then 0.5% by weight of lithium nitrate (LiNO3) was added to prepare the electrolyte for lithium secondary batteries of the present invention.

[0234] (Preparation of secondary batteries)

[0235] The lithium secondary battery was prepared in the same manner as in Example 7, except that 4.77 g of the electrolyte for lithium secondary batteries prepared above was injected (see Table 1 below).

[0236] Example 10.

[0237] (Positive electrode preparation)

[0238] A positive electrode active material (LiFePO4), a conductive agent (carbon black), and a binder (polyvinylidene fluoride, PVDF) were added to N-methyl-2-pyrrolidone (NMP) as a solvent in a weight ratio of 96:1:3 to prepare a positive electrode active material slurry (67% by weight solids). This positive electrode active material slurry was then used to coat a 15 μm thick positive electrode current collector (Al film; total surface area of ​​the positive electrode current collector: 312 cm²).2 The cathode was prepared by drying and rolling (cathode loading: 0.064 g / cm³). 2 Based on the loading capacity of the positive electrode single side: 0.032 g / cm³ 2 (Porosity of the cathode material mixture layer: 24%).

[0239] (Electrolyte preparation)

[0240] LiPF6 was dissolved in an organic solvent in which γ-butyrolactone and ethylene carbonate were mixed in a volume ratio of 70:30 to make the concentration of LiPF6 1.0 M, and then 0.5% by weight of lithium nitrate (LiNO3) was added to prepare the electrolyte for lithium secondary batteries of the present invention.

[0241] (Preparation of secondary batteries)

[0242] A lithium secondary battery was prepared in the same manner as in Example 7, except that 3.43 g of the electrolyte for lithium secondary batteries prepared above was injected (see Table 1 below).

[0243] Example 11.

[0244] (Electrolyte preparation)

[0245] LiPF6 was dissolved in an organic solvent in which γ-butyrolactone and ethylene carbonate were mixed in a volume ratio of 70:30 to make the concentration of LiPF6 1.0 M, and then 0.5% by weight of lithium nitrate (LiNO3) was added to prepare the electrolyte for lithium secondary batteries of the present invention.

[0246] (Preparation of secondary batteries)

[0247] A lithium secondary battery was prepared in the same manner as in Example 10, except that 4.55 g of the electrolyte for lithium secondary batteries prepared above was injected (see Table 1 below).

[0248] Example 12.

[0249] (Electrolyte preparation)

[0250] LiPF6 was dissolved in an organic solvent in which γ-butyrolactone and ethylene carbonate were mixed in a volume ratio of 70:30 to make the concentration of LiPF6 1.0 M, and then 0.5% by weight of lithium nitrate (LiNO3) was added to prepare the electrolyte for lithium secondary batteries of the present invention.

[0251] (Preparation of secondary batteries)

[0252] A lithium secondary battery was prepared in the same manner as in Example 10, except that 6.07 g of the electrolyte for lithium secondary batteries prepared above was injected (see Table 1 below).

[0253] Example 13.

[0254] (Positive electrode preparation)

[0255] A positive electrode active material (LiFePO4), a conductive agent (carbon black), and a binder (polyvinylidene fluoride, PVDF) were added to N-methyl-2-pyrrolidone (NMP) as a solvent in a weight ratio of 96:1:3 to prepare a positive electrode active material slurry (67% by weight solids). This positive electrode active material slurry was then used to coat a 15 μm thick positive electrode current collector (Al film; total surface area of ​​the positive electrode current collector: 435 cm²). 2 The cathode was prepared by drying and rolling (cathode loading: 0.048 g / cm³). 2 Based on the loading capacity of the positive electrode single side: 0.024 g / cm³ 2 (Porosity of the cathode material mixture layer: 24%).

[0256] (Anode preparation)

[0257] A negative electrode active material (100% artificial graphite), CMC-SBR as a binder, and carbon black as a conductive agent were added to distilled water as a solvent in a weight ratio of 96:3.5:0.5 to prepare a negative electrode active material slurry (solid content 53 wt%). This negative electrode active material slurry was then coated onto an 8 μm thick negative electrode current collector (Cu film), dried, and rolled to prepare the negative electrode (porosity of the negative electrode material mixture layer: 26%).

[0258] (Electrolyte preparation)

[0259] LiPF6 was dissolved in an organic solvent in which γ-butyrolactone and ethylene carbonate were mixed in a volume ratio of 70:30 to make the concentration of LiPF6 1.0 M, and then 0.25% by weight of lithium nitrate (LiNO3) was added to prepare the electrolyte for lithium secondary batteries of the present invention.

[0260] (Preparation of secondary batteries)

[0261] Electrode assemblies were prepared by a conventional method in which the positive and negative electrodes prepared by the above method were stacked together with a polyethylene porous membrane. The assemblies were then housed in a pouch-type secondary battery casing, and 4.86 g of the electrolyte for lithium secondary batteries prepared above was injected to prepare a lithium secondary battery (see Table 1 below).

[0262] Example 14.

[0263] (Positive electrode preparation)

[0264] A positive electrode active material (LiFePO4), a conductive agent (carbon black), and a binder (polyvinylidene fluoride, PVDF) were added to N-methyl-2-pyrrolidone (NMP) as a solvent in a weight ratio of 96:1:3 to prepare a positive electrode active material slurry (67% by weight solids). This positive electrode active material slurry was then used to coat a 15 μm thick positive electrode current collector (Al film; total surface area of ​​the positive electrode current collector: 435 cm²). 2 The cathode was prepared by drying and rolling (cathode loading: 0.064 g / cm³). 2 Based on the loading capacity of the positive electrode single side: 0.032 g / cm³ 2 (Porosity of the cathode material mixture layer: 24%).

[0265] (Anode preparation)

[0266] A negative electrode active material (100% artificial graphite), CMC-SBR as a binder, and carbon black as a conductive agent were added to distilled water as a solvent in a weight ratio of 96:3.5:0.5 to prepare a negative electrode active material slurry (solid content 53 wt%). This negative electrode active material slurry was then coated onto an 8 μm thick negative electrode current collector (Cu film), dried, and rolled to prepare the negative electrode (porosity of the negative electrode material mixture layer: 26%).

[0267] (Electrolyte preparation)

[0268] LiPF6 was dissolved in an organic solvent in which γ-butyrolactone and ethylene carbonate were mixed in a volume ratio of 70:30 to make the concentration of LiPF6 1.0 M, and then 0.25% by weight of lithium nitrate (LiNO3) was added to prepare the electrolyte for lithium secondary batteries of the present invention.

[0269] (Preparation of secondary batteries)

[0270] Electrode assemblies were prepared by a conventional method in which the positive and negative electrodes prepared by the above method were stacked together with a polyethylene porous membrane. The assemblies were then housed in a pouch-type secondary battery casing, and 4.86 g of the electrolyte for lithium secondary batteries prepared above was injected to prepare a lithium secondary battery (see Table 1 below).

[0271] Example 15.

[0272] (Positive electrode preparation)

[0273] A positive electrode active material (LiFePO4), a conductive agent (carbon black), and a binder (polyvinylidene fluoride, PVDF) were added to N-methyl-2-pyrrolidone (NMP) as a solvent in a weight ratio of 96:1:3 to prepare a positive electrode active material slurry (67% by weight solids). This positive electrode active material slurry was then used to coat a 15 μm thick positive electrode current collector (Al film; total surface area of ​​the positive electrode current collector: 435 cm²). 2 The cathode was prepared by drying and rolling (cathode loading: 0.048 g / cm³). 2 Based on the loading capacity of the positive electrode single side: 0.024 g / cm³ 2 (Porosity of the cathode material mixture layer: 24%).

[0274] (Anode preparation)

[0275] A negative electrode active material (100% artificial graphite), CMC-SBR as a binder, and carbon black as a conductive agent were added to distilled water as a solvent in a weight ratio of 96:3.5:0.5 to prepare a negative electrode active material slurry (solid content 53 wt%). This negative electrode active material slurry was then coated onto an 8 μm thick negative electrode current collector (Cu film), dried, and rolled to prepare the negative electrode (porosity of the negative electrode material mixture layer: 26%).

[0276] (Electrolyte preparation)

[0277] LiPF6 was dissolved in an organic solvent in which γ-butyrolactone and ethylene carbonate were mixed in a volume ratio of 70:30 to make the concentration of LiPF6 1.0 M, and then 3.0 wt% of lithium nitrate (LiNO3) was added to prepare the electrolyte for lithium secondary batteries of the present invention.

[0278] (Preparation of secondary batteries)

[0279] Electrode assemblies were prepared by a conventional method in which the positive and negative electrodes prepared by the above method were stacked together with a polyethylene porous membrane. The assemblies were then housed in a pouch-type secondary battery casing and 4.65 g of the electrolyte for lithium secondary batteries prepared above was injected to prepare a lithium secondary battery (see Table 1 below).

[0280] Example 16.

[0281] (Positive electrode preparation)

[0282] A positive electrode active material (LiFePO4), a conductive agent (carbon black), and a binder (polyvinylidene fluoride, PVDF) were added to N-methyl-2-pyrrolidone (NMP) as a solvent in a weight ratio of 96:1:3 to prepare a positive electrode active material slurry (67% by weight solids). This positive electrode active material slurry was then used to coat a 15 μm thick positive electrode current collector (Al film; total surface area of ​​the positive electrode current collector: 435 cm²). 2 The cathode was prepared by drying and rolling (cathode loading: 0.064 g / cm³). 2 Based on the loading capacity of the positive electrode single side: 0.032 g / cm³ 2 (Porosity of the cathode material mixture layer: 24%).

[0283] (Anode preparation)

[0284] A negative electrode active material (100% artificial graphite), CMC-SBR as a binder, and carbon black as a conductive agent were added to distilled water as a solvent in a weight ratio of 96:3.5:0.5 to prepare a negative electrode active material slurry (solid content 53 wt%). This negative electrode active material slurry was then coated onto an 8 μm thick negative electrode current collector (Cu film), dried, and rolled to prepare the negative electrode (porosity of the negative electrode material mixture layer: 26%).

[0285] (Electrolyte preparation)

[0286] LiPF6 was dissolved in an organic solvent in which γ-butyrolactone and ethylene carbonate were mixed in a volume ratio of 70:30 to make the concentration of LiPF6 1.0 M, and then 3.0 wt% of lithium nitrate (LiNO3) was added to prepare the electrolyte for lithium secondary batteries of the present invention.

[0287] (Preparation of secondary batteries)

[0288] Electrode assemblies were prepared by a conventional method in which the positive and negative electrodes prepared by the above method were stacked together with a polyethylene porous membrane. The assemblies were then housed in a pouch-type secondary battery casing and 4.65 g of the electrolyte for lithium secondary batteries prepared above was injected to prepare a lithium secondary battery (see Table 1 below).

[0289] Example 17.

[0290] (Positive electrode preparation)

[0291] A positive electrode active material (LiFePO4), a conductive agent (carbon black), and a binder (polyvinylidene fluoride, PVDF) were added to N-methyl-2-pyrrolidone (NMP) as a solvent in a weight ratio of 96:1:3 to prepare a positive electrode active material slurry (67% by weight solids). This positive electrode active material slurry was then used to coat a 15 μm thick positive electrode current collector (Al film; total surface area of ​​the positive electrode current collector: 435 cm²). 2 The cathode was prepared by drying and rolling (cathode loading: 0.048 g / cm³). 2 Based on the loading capacity of the positive electrode single side: 0.024 g / cm³ 2 (Porosity of the cathode material mixture layer: 24%).

[0292] (Anode preparation)

[0293] A negative electrode active material (100% artificial graphite), CMC-SBR as a binder, and carbon black as a conductive agent were added to distilled water as a solvent in a weight ratio of 96:3.5:0.5 to prepare a negative electrode active material slurry (solid content 53 wt%). This negative electrode active material slurry was then coated onto an 8 μm thick negative electrode current collector (Cu film), dried, and rolled to prepare the negative electrode (porosity of the negative electrode material mixture layer: 26%).

[0294] (Electrolyte preparation)

[0295] LiPF6 was dissolved in an organic solvent in which γ-butyrolactone and ethylene carbonate were mixed in a volume ratio of 70:30 to make the concentration of LiPF6 1.0 M, and then 0.5% by weight of lithium nitrate (LiNO3) was added to prepare the electrolyte for lithium secondary batteries of the present invention.

[0296] (Preparation of secondary batteries)

[0297] Electrode assemblies were prepared by a conventional method in which the positive and negative electrodes prepared by the above method were stacked together with a polyethylene porous membrane. The assemblies were then housed in a pouch-type secondary battery casing, and 8.29 g of the electrolyte for lithium secondary batteries prepared above was injected to prepare a lithium secondary battery (see Table 1 below).

[0298] Example 18.

[0299] (Electrolyte preparation)

[0300] LiPF6 was dissolved in an organic solvent in which γ-butyrolactone and ethylene carbonate were mixed in a volume ratio of 70:30 to make the concentration of LiPF6 1.0 M, and then 1.0 wt% of lithium nitrate (LiNO3) was added to prepare the electrolyte for lithium secondary batteries of the present invention.

[0301] (Preparation of secondary batteries)

[0302] A lithium secondary battery was prepared in the same manner as in Example 17, except that 8.29 g of the electrolyte for lithium secondary batteries prepared above was injected (see Table 1 below).

[0303] Example 19.

[0304] (Electrolyte preparation)

[0305] LiPF6 was dissolved in an organic solvent in which γ-butyrolactone and ethylene carbonate were mixed in a volume ratio of 70:30 to make the concentration of LiPF6 1.0 M, and then 2.0 wt% of lithium nitrate (LiNO3) was added to prepare the electrolyte for lithium secondary batteries of the present invention.

[0306] (Preparation of secondary batteries)

[0307] A lithium secondary battery was prepared in the same manner as in Example 17, except that 8.29 g of the electrolyte for lithium secondary batteries prepared above was injected (see Table 1 below).

[0308] Example 20.

[0309] (Electrolyte preparation)

[0310] LiPF6 was dissolved in an organic solvent in which γ-butyrolactone and ethylene carbonate were mixed in a volume ratio of 70:30 to make the concentration of LiPF6 1.0 M, and then 3.0 wt% of lithium nitrate (LiNO3) was added to prepare the electrolyte for lithium secondary batteries of the present invention.

[0311] (Preparation of secondary batteries)

[0312] A lithium secondary battery was prepared in the same manner as in Example 17, except that 8.29 g of the electrolyte for lithium secondary batteries prepared above was injected (see Table 1 below).

[0313] Example 21.

[0314] (Positive electrode preparation)

[0315] A positive electrode active material (LiFePO4), a conductive agent (carbon black), and a binder (polyvinylidene fluoride, PVDF) were added to N-methyl-2-pyrrolidone (NMP) as a solvent in a weight ratio of 96:1:3 to prepare a positive electrode active material slurry (67% by weight solids). This positive electrode active material slurry was then used to coat a 15 μm thick positive electrode current collector (Al film; total surface area of ​​the positive electrode current collector: 280 cm²). 2 The cathode was prepared by drying and rolling (cathode loading: 0.048 g / cm³). 2Based on the loading capacity of the positive electrode single side: 0.024 g / cm³ 2 (Porosity of the cathode material mixture layer: 24%).

[0316] (Anode preparation)

[0317] A negative electrode active material (100% artificial graphite), CMC-SBR as a binder, and carbon black as a conductive agent were added to distilled water as a solvent in a weight ratio of 96:3.5:0.5 to prepare a negative electrode active material slurry (solid content 53 wt%). This negative electrode active material slurry was then coated onto an 8 μm thick negative electrode current collector (Cu film), dried, and rolled to prepare the negative electrode (porosity of the negative electrode material mixture layer: 26%).

[0318] (Electrolyte preparation)

[0319] LiPF6 was dissolved in an organic solvent in which γ-butyrolactone and ethylene carbonate were mixed in a volume ratio of 70:30 to make the concentration of LiPF6 1.0 M, and then 1.0 wt% of lithium nitrate (LiNO3) was added to prepare the electrolyte for lithium secondary batteries of the present invention.

[0320] (Preparation of secondary batteries)

[0321] Electrode assemblies were prepared by a conventional method in which the positive and negative electrodes prepared by the above method were stacked together with a polyethylene porous membrane. The assemblies were then housed in a pouch-type secondary battery casing, and 3.65 g of the electrolyte for lithium secondary batteries prepared above was injected to prepare a lithium secondary battery (see Table 1 below).

[0322] Example 22.

[0323] (Positive electrode preparation)

[0324] A positive electrode active material (LiFePO4), a conductive agent (carbon black), and a binder (polyvinylidene fluoride, PVDF) were added to N-methyl-2-pyrrolidone (NMP) as a solvent in a weight ratio of 96:1:3 to prepare a positive electrode active material slurry (67% by weight solids). This positive electrode active material slurry was then used to coat a 15 μm thick positive electrode current collector (Al film; total surface area of ​​the positive electrode current collector: 465 cm²). 2 The cathode was prepared by drying and rolling (cathode loading: 0.048 g / cm³). 2 Based on the loading capacity of the positive electrode single side: 0.024 g / cm³ 2 (Porosity of the cathode material mixture layer: 24%).

[0325] (Preparation of secondary batteries)

[0326] A lithium secondary battery was prepared in the same manner as in Example 21, except that the positive electrode prepared above was used (see Table 1 below).

[0327] Example 23.

[0328] (Positive electrode preparation)

[0329] A positive electrode active material (LiFePO4), a conductive agent (carbon black), and a binder (polyvinylidene fluoride, PVDF) were added to N-methyl-2-pyrrolidone (NMP) as a solvent in a weight ratio of 96:1:3 to prepare a positive electrode active material slurry (67% by weight solids). This positive electrode active material slurry was then used to coat a 15 μm thick positive electrode current collector (Al film; total surface area of ​​the positive electrode current collector: 435 cm²). 2 The cathode was prepared by drying and rolling (cathode loading: 0.030 g / cm³). 2 Based on the loading capacity of the positive electrode single side: 0.015 g / cm³ 2 (Porosity of the cathode material mixture layer: 24%).

[0330] (Preparation of secondary batteries)

[0331] A lithium secondary battery was prepared in the same manner as in Example 21, except that the positive electrode prepared above was used (see Table 1 below).

[0332] Example 24.

[0333] (Positive electrode preparation)

[0334] A positive electrode active material (LiFePO4), a conductive agent (carbon black), and a binder (polyvinylidene fluoride, PVDF) were added to N-methyl-2-pyrrolidone (NMP) as a solvent in a weight ratio of 96:1:3 to prepare a positive electrode active material slurry (67% by weight solids). This positive electrode active material slurry was then used to coat a 15 μm thick positive electrode current collector (Al film; total surface area of ​​the positive electrode current collector: 435 cm²). 2 The cathode was prepared by drying and rolling (cathode loading: 0.072 g / cm³). 2 Based on the loading capacity of the positive electrode single side: 0.036 g / cm³ 2 (Porosity of the cathode material mixture layer: 24%).

[0335] (Preparation of secondary batteries)

[0336] A lithium secondary battery was prepared in the same manner as in Example 21, except that the positive electrode prepared above was used (see Table 1 below).

[0337] Example 25.

[0338] (Positive electrode preparation)

[0339] A positive electrode active material (LiFePO4), a conductive agent (carbon black), and a binder (polyvinylidene fluoride, PVDF) were added to N-methyl-2-pyrrolidone (NMP) as a solvent in a weight ratio of 96:1:3 to prepare a positive electrode active material slurry (67% by weight solids). This positive electrode active material slurry was then used to coat a 15 μm thick positive electrode current collector (Al film; total surface area of ​​the positive electrode current collector: 435 cm²). 2 The cathode was prepared by drying and rolling (cathode loading: 0.048 g / cm³). 2 Based on the loading capacity of the positive electrode single side: 0.024 g / cm³ 2 (Porosity of the cathode material mixture layer: 24%).

[0340] (Electrolyte preparation)

[0341] LiPF6 was dissolved in an organic solvent in which γ-butyrolactone and ethylene carbonate were mixed in a volume ratio of 70:30 to make the concentration of LiPF6 1.0 M, and then 1.0 wt% of lithium nitrate (LiNO3) was added to prepare the electrolyte for lithium secondary batteries of the present invention.

[0342] (Preparation of secondary batteries)

[0343] A lithium secondary battery was prepared in the same manner as in Example 21, except that the positive electrode prepared above was used and 2.98 g of the electrolyte prepared above for lithium secondary batteries was injected (see Table 1 below).

[0344] Example 26.

[0345] (Positive electrode preparation)

[0346] A positive electrode active material (LiFePO4), a conductive agent (carbon black), and a binder (polyvinylidene fluoride, PVDF) were added to N-methyl-2-pyrrolidone (NMP) as a solvent in a weight ratio of 96:1:3 to prepare a positive electrode active material slurry (67% by weight solids). This positive electrode active material slurry was then used to coat a 15 μm thick positive electrode current collector (Al film; total surface area of ​​the positive electrode current collector: 435 cm²). 2 The cathode was prepared by drying and rolling (cathode loading: 0.048 g / cm³). 2 Based on the loading capacity of the positive electrode single side: 0.024 g / cm³ 2 (Porosity of the cathode material mixture layer: 24%).

[0347] (Electrolyte preparation)

[0348] LiPF6 was dissolved in an organic solvent in which γ-butyrolactone and ethylene carbonate were mixed in a volume ratio of 70:30 to make the concentration of LiPF6 1.0 M, and then 1.0 wt% of lithium nitrate (LiNO3) was added to prepare the electrolyte for lithium secondary batteries of the present invention.

[0349] (Preparation of secondary batteries)

[0350] A lithium secondary battery was prepared in the same manner as in Example 21, except that the positive electrode prepared above was used and 9.95 g of the electrolyte prepared above for lithium secondary batteries was injected (see Table 1 below).

[0351] Comparative Example 1.

[0352] (Positive electrode preparation)

[0353] A positive electrode active material (LiFePO4), a conductive agent (carbon black), and a binder (polyvinylidene fluoride, PVDF) were added to N-methyl-2-pyrrolidone (NMP) as a solvent in a weight ratio of 96:1:3 to prepare a positive electrode active material slurry (67% by weight solids). This positive electrode active material slurry was then used to coat a 15 μm thick positive electrode current collector (Al film; total surface area of ​​the positive electrode current collector: 312 cm²). 2 The cathode was prepared by drying and rolling (cathode loading: 0.032 g / cm³). 2 Based on the loading capacity of the positive electrode single side: 0.016 g / cm³ 2 (Porosity of the cathode material mixture layer: 24%).

[0354] (Anode preparation)

[0355] A negative electrode active material (100% artificial graphite), CMC-SBR as a binder, and carbon black as a conductive agent were added to distilled water as a solvent in a weight ratio of 96:3.5:0.5 to prepare a negative electrode active material slurry (solid content 53 wt%). This negative electrode active material slurry was then coated onto an 8 μm thick negative electrode current collector (Cu film), dried, and rolled to prepare the negative electrode (porosity of the negative electrode material mixture layer: 26%).

[0356] (Electrolyte preparation)

[0357] LiPF6 was dissolved in an organic solvent in which γ-butyrolactone and ethylene carbonate were mixed in a volume ratio of 70:30 to make the concentration of LiPF6 1.0 M, and then 4.0 wt% of lithium nitrate (LiNO3) was added to prepare the electrolyte for lithium secondary batteries of the present invention.

[0358] (Preparation of secondary batteries)

[0359] Electrode assemblies were prepared by a conventional method in which the positive and negative electrodes prepared by the above method were stacked together with a polyethylene porous membrane. The assemblies were then housed in a pouch-type secondary battery casing and 8.50 g of the electrolyte for lithium secondary batteries prepared above was injected to prepare a lithium secondary battery (see Table 1 below).

[0360] Compare Example 2.

[0361] (Positive electrode preparation)

[0362] A positive electrode active material (LiFePO4), a conductive agent (carbon black), and a binder (polyvinylidene fluoride, PVDF) were added to N-methyl-2-pyrrolidone (NMP) as a solvent in a weight ratio of 96:1:3 to prepare a positive electrode active material slurry (67% by weight solids). This positive electrode active material slurry was then used to coat a 15 μm thick positive electrode current collector (Al film; total surface area of ​​the positive electrode current collector: 312 cm²). 2 The cathode was prepared by drying and rolling (cathode loading: 0.064 g / cm³). 2 Based on the loading capacity of the positive electrode single side: 0.032 g / cm³ 2 (Porosity of the cathode material mixture layer: 24%).

[0363] (Anode preparation)

[0364] A negative electrode active material (100% artificial graphite), CMC-SBR as a binder, and carbon black as a conductive agent were added to distilled water as a solvent in a weight ratio of 96:3.5:0.5 to prepare a negative electrode active material slurry (solid content 53 wt%). This negative electrode active material slurry was then coated onto an 8 μm thick negative electrode current collector (Cu film), dried, and rolled to prepare the negative electrode (porosity of the negative electrode material mixture layer: 26%).

[0365] (Electrolyte preparation)

[0366] LiPF6 was dissolved in an organic solvent in which γ-butyrolactone and ethylene carbonate were mixed in a volume ratio of 70:30 to make the concentration of LiPF6 1.0 M, and then 11.0 wt% of lithium nitrate (LiNO3) was added to prepare the electrolyte for lithium secondary batteries of the present invention.

[0367] (Preparation of secondary batteries)

[0368] Electrode assemblies were prepared by a conventional method in which the positive and negative electrodes prepared by the above method were stacked together with a polyethylene porous membrane. The assemblies were then housed in a pouch-type secondary battery casing, and 4.77 g of the electrolyte for lithium secondary batteries prepared above was injected to prepare a lithium secondary battery (see Table 1 below).

[0369] Comparative Example 3.

[0370] (Positive electrode preparation)

[0371] A positive electrode active material (LiFePO4), a conductive agent (carbon black), and a binder (polyvinylidene fluoride, PVDF) were added to N-methyl-2-pyrrolidone (NMP) as a solvent in a weight ratio of 96:1:3 to prepare a positive electrode active material slurry (67% by weight solids). This positive electrode active material slurry was then used to coat a 15 μm thick positive electrode current collector (Al film; total surface area of ​​the positive electrode current collector: 435 cm²). 2 The cathode was prepared by drying and rolling (cathode loading: 0.048 g / cm³). 2 Based on the loading capacity of the positive electrode single side: 0.024 g / cm³ 2 (Porosity of the cathode material mixture layer: 24%).

[0372] (Anode preparation)

[0373] A negative electrode active material (100% artificial graphite), CMC-SBR as a binder, and carbon black as a conductive agent were added to distilled water as a solvent in a weight ratio of 96:3.5:0.5 to prepare a negative electrode active material slurry (solid content 53 wt%). This negative electrode active material slurry was then coated onto an 8 μm thick negative electrode current collector (Cu film), dried, and rolled to prepare the negative electrode (porosity of the negative electrode material mixture layer: 26%).

[0374] (Electrolyte preparation)

[0375] LiPF6 was dissolved in an organic solvent in which γ-butyrolactone and ethylene carbonate were mixed in a volume ratio of 70:30 to make the concentration of LiPF6 1.0 M, and then 0.025% by weight of lithium nitrate (LiNO3) was added to prepare the electrolyte for lithium secondary batteries of the present invention.

[0376] (Preparation of secondary batteries)

[0377] Electrode assemblies were prepared by a conventional method in which the positive and negative electrodes prepared by the above method were stacked together with a polyethylene porous membrane. The assemblies were then housed in a pouch-type secondary battery casing, and 3.48 g of the electrolyte for lithium secondary batteries prepared above was injected to prepare a lithium secondary battery (see Table 1 below).

[0378] Comparative Example 4.

[0379] (Positive electrode preparation)

[0380] A positive electrode active material (LiFePO4), a conductive agent (carbon black), and a binder (polyvinylidene fluoride, PVDF) were added to N-methyl-2-pyrrolidone (NMP) as a solvent in a weight ratio of 96:1:3 to prepare a positive electrode active material slurry (67% by weight solids). This positive electrode active material slurry was then used to coat a 15 μm thick positive electrode current collector (Al film; total surface area of ​​the positive electrode current collector: 435 cm²). 2 The cathode was prepared by drying and rolling (cathode loading: 0.048 g / cm³). 2 Based on the loading capacity of the positive electrode single side: 0.024 g / cm³ 2 (Porosity of the cathode material mixture layer: 24%).

[0381] (Anode preparation)

[0382] A negative electrode active material (100% artificial graphite), CMC-SBR as a binder, and carbon black as a conductive agent were added to distilled water as a solvent in a weight ratio of 96:3.5:0.5 to prepare a negative electrode active material slurry (solid content 53 wt%). This negative electrode active material slurry was then coated onto an 8 μm thick negative electrode current collector (Cu film), dried, and rolled to prepare the negative electrode (porosity of the negative electrode material mixture layer: 26%).

[0383] (Electrolyte preparation)

[0384] LiPF6 was dissolved in an organic solvent in which γ-butyrolactone and ethylene carbonate were mixed in a volume ratio of 70:30 to make the concentration of LiPF6 1.0 M, and then 6.5% by weight of lithium nitrate (LiNO3) was added to prepare the electrolyte for lithium secondary batteries of the present invention.

[0385] (Preparation of secondary batteries)

[0386] Electrode assemblies were prepared by a conventional method in which the positive and negative electrodes prepared by the above method were stacked together with a polyethylene porous membrane. The assemblies were then housed in a pouch-type secondary battery casing, and 8.29 g of the electrolyte for lithium secondary batteries prepared above was injected to prepare a lithium secondary battery (see Table 1 below).

[0387] Comparative Example 5.

[0388] (Positive electrode preparation)

[0389] A positive electrode active material (LiFePO4), a conductive agent (carbon black), and a binder (polyvinylidene fluoride, PVDF) were added to N-methyl-2-pyrrolidone (NMP) as a solvent in a weight ratio of 96:1:3 to prepare a positive electrode active material slurry (67% by weight solids). This positive electrode active material slurry was then used to coat a 15 μm thick positive electrode current collector (Al film; total surface area of ​​the positive electrode current collector: 435 cm²). 2 The cathode was prepared by drying and rolling (cathode loading: 0.064 g / cm³). 2 Based on the loading capacity of the positive electrode single side: 0.032 g / cm³ 2 (Porosity of the cathode material mixture layer: 24%).

[0390] (Anode preparation)

[0391] A negative electrode active material (100% artificial graphite), CMC-SBR as a binder, and carbon black as a conductive agent were added to distilled water as a solvent in a weight ratio of 96:3.5:0.5 to prepare a negative electrode active material slurry (solid content 53 wt%). This negative electrode active material slurry was then coated onto an 8 μm thick negative electrode current collector (Cu film), dried, and rolled to prepare the negative electrode (porosity of the negative electrode material mixture layer: 26%).

[0392] (Electrolyte preparation)

[0393] LiPF6 was dissolved in an organic solvent in which γ-butyrolactone and ethylene carbonate were mixed in a volume ratio of 70:30 to make the concentration of LiPF6 1.0 M, and then 0.02% by weight of lithium nitrate (LiNO3) was added to prepare the electrolyte for lithium secondary batteries of the present invention.

[0394] (Preparation of secondary batteries)

[0395] Electrode assemblies were prepared by a conventional method in which the positive and negative electrodes prepared by the above method were stacked together with a polyethylene porous membrane. The assemblies were then housed in a pouch-type secondary battery casing and 3.00 g of the electrolyte for lithium secondary batteries prepared above was injected to prepare a lithium secondary battery (see Table 1 below).

[0396] Comparative Example 6.

[0397] (Positive electrode preparation)

[0398] A positive electrode active material (LiFePO4), a conductive agent (carbon black), and a binder (polyvinylidene fluoride, PVDF) were added to N-methyl-2-pyrrolidone (NMP) as a solvent in a weight ratio of 96:1:3 to prepare a positive electrode active material slurry (67% by weight solids). This positive electrode active material slurry was then used to coat a 15 μm thick positive electrode current collector (Al film; total surface area of ​​the positive electrode current collector: 435 cm²). 2 The cathode was prepared by drying and rolling (cathode loading: 0.064 g / cm³). 2 Based on the loading capacity of the positive electrode single side: 0.032 g / cm³ 2 (Porosity of the cathode material mixture layer: 24%).

[0399] (Anode preparation)

[0400] A negative electrode active material (100% artificial graphite), CMC-SBR as a binder, and carbon black as a conductive agent were added to distilled water as a solvent in a weight ratio of 96:3.5:0.5 to prepare a negative electrode active material slurry (solid content 53 wt%). This negative electrode active material slurry was then coated onto an 8 μm thick negative electrode current collector (Cu film), dried, and rolled to prepare the negative electrode (porosity of the negative electrode material mixture layer: 26%).

[0401] (Electrolyte preparation)

[0402] LiPF6 was dissolved in an organic solvent in which γ-butyrolactone and ethylene carbonate were mixed in a volume ratio of 70:30 to make the concentration of LiPF6 1.0 M, and then 12.0 wt% lithium nitrate (LiNO3) was added to prepare the electrolyte for lithium secondary batteries of the present invention.

[0403] (Preparation of secondary batteries)

[0404] Electrode assemblies were prepared by a conventional method in which the positive and negative electrodes prepared by the above method were stacked together with a polyethylene porous membrane. The assemblies were then housed in a pouch-type secondary battery casing, and 6.43 g of the lithium secondary battery electrolyte prepared above was injected to prepare a lithium secondary battery (see Table 1 below).

[0405] [Table 1]

[0406]

[0407] [Experimental Example]

[0408] Experimental Example 1. Evaluation of High-Temperature (45°C) Cycling Characteristics

[0409] The lithium secondary batteries prepared in the examples and comparative examples were each charged at a rate of 0.1C to 64% of their state of charge (SOC) at a high temperature (55°C), and then subjected to aging (48 hours) and degassing processes for formation.

[0410] After formation, each lithium secondary battery was charged to 3.8 V at a constant current / constant voltage rate of 0.1 C at room temperature (25°C) and discharged to 2.5 V at a constant current rate of 0.33 C to check the initial capacity.

[0411] Subsequently, each lithium-ion battery was charged to 3.8 V at a constant current / constant voltage rate of 0.33 C under high temperature (45°C) and discharged to 2.5 V at a constant current rate of 0.33 C, which was set as one cycle. This cycle was performed for 100 cycles, and then the discharge capacity was measured. The operation of the lithium-ion batteries was carried out using a PNE-0506 charge / discharge device (manufacturer: PNE solution).

[0412] The capacity retention rate (%) after high-temperature cycling was calculated using the ratio of the capacity after the 100th discharge to the initial capacity obtained, and the results are shown in Table 2 below.

[0413] Experimental Example 2. Evaluation of Low-Temperature (-10°C) Cycling Characteristics

[0414] The lithium secondary batteries prepared in the examples and comparative examples were each charged to 64% SOC at a rate of 0.1 C at a high temperature (55°C), and then subjected to aging (48 hours) and degassing processes for formation.

[0415] After formation, each lithium secondary battery was charged to 3.8 V at a constant current / constant voltage rate of 0.1 C at room temperature (25°C) and discharged to 2.5 V at a constant current rate of 0.33 C to check the initial capacity.

[0416] Subsequently, each lithium-ion battery was charged to 3.8 V at a constant current / constant voltage rate of 0.2 C under low temperature (-10°C) and discharged to 2.0 V at a constant current rate of 0.33 C, which was set as one cycle. This cycle was performed for 200 cycles, and then the discharge capacity was measured. The lithium-ion batteries were operated using a PNE-0506 charge / discharge apparatus (manufacturer: PNE solution).

[0417] The capacity retention rate (%) after cryogenic cycling was calculated using the obtained initial capacity and the capacity after the 200th discharge, and the results are shown in Table 2 below.

[0418] [Table 2]

[0419]

[0420] Referring to Table 2, it can be confirmed that the capacity retention rate after high-temperature cycling and the capacity retention rate after low-temperature cycling are both improved compared with the lithium secondary batteries of Comparative Examples 1 to 6.

[0421] Although the invention has been described above with reference to preferred embodiments, those skilled in the art will understand that various modifications and changes can be made without departing from the spirit and scope of the invention as set forth in the appended claims. Therefore, the scope of the invention should not be limited to the details described in the specification, but should be determined by the claims.

Claims

1. A lithium secondary battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode comprises lithium iron phosphate as a positive electrode active material, and the electrolyte comprises a lithium salt, a first organic solvent, a second organic solvent and an additive, in, the first organic solvent is a cyclic lactone compound, and based on the total weight of the electrolyte, the content of the first organic solvent is 39 wt% to 80 wt%, the second organic solvent is a carbonate-based organic solvent, the additive is lithium nitrate (LiNO3) and satisfies the following Relational Expression 1: [Relational Expression 1] wherein, in Relational Expression 1, A is the total mass of the electrolyte injected into the lithium secondary battery, unit is g, B is the content of lithium nitrate (LiNO3) contained in the injected electrolyte, unit is wt%, C represents the loading of the positive electrode, in g / cm³. 2 ,and D is the total surface area of ​​the positive electrode current collector, in cm². 2 .

2. The lithium secondary battery as described in claim 1, wherein, the lithium iron phosphate comprises a compound represented by Formula 1: [Formula 1] Li 1+a Fe x M y (PO 4-b )X’ b wherein, in Formula 1, M is any one selected from the group consisting of aluminum (Al), magnesium (Mg), nickel (Ni), cobalt (Co), manganese (Mn), titanium (Ti), gallium (Ga), copper (Cu), vanadium (V), niobium (Nb), zirconium (Zr), cerium (Ce), indium (In), zinc (Zn) and yttrium (Y); X' is at least one element selected from the group consisting of fluorine (F), sulfur (S) and nitrogen (N), and -0.5≤a≤0.5, 0<x≤1, 0≤y≤1 and 0≤b≤0.

3.

3. The lithium secondary battery as described in claim 2, wherein, The lithium iron phosphate is lithium iron phosphate (LiFePO4) or lithium manganese iron phosphate (LiFeMnPO4).

4. The lithium secondary battery as described in claim 1, wherein, The cyclic lactone compound comprises γ-butyrolactone.

5. The lithium secondary battery as described in claim 1, wherein, The carbonate-based organic solvent is a cyclic carbonate-based organic solvent.

6. The lithium secondary battery as described in claim 1, wherein, The first organic solvent and the second organic solvent are present in a volume ratio of 50:50 to 99:

1.

7. The lithium secondary battery as described in claim 1, wherein, In Relational Expression 1, A is 3.0 g to 8.5 g.

8. The lithium secondary battery as described in claim 1, wherein, In equation 1, C is 0.032 g / cm³. 2 Up to 0.064 g / cm 2 .

9. The lithium secondary battery as described in claim 1, wherein, In relation 1, D is 310 cm. 2 Up to 450 cm 2 .

10. The lithium secondary battery as described in claim 1, wherein, The negative electrode comprises a carbon-based active material, a silicon-based active material, or a mixture of a carbon-based active material and a silicon-based active material.

11. The lithium secondary battery as described in claim 1, wherein, The capacity of the lithium secondary battery is 1,000 mAh to 3,000 mAh.

Citation Information

Patent Citations

  • Producing method of processed food having controlled food texture using 3D printing and processed food by the same

    KR1020240165719A

  • Electrolyte for lithium ion secondary battery and lithium ion secondary battery

    CN117039144A